PERBANDINGAN KADAR UREUM DARAH SEBELUM DAN SESUDAH HEMODIALISA PADA PENDERITA GAGAL GINJAL DI RSUD MAJENANG - Sri Lestari; Dini Puspodewi; Meka Faizal Farabi (LPPM Universitas Abdurrab, 2026)
Chronic kidney disease (CKD) is a progressive and irreversible decline in kidney function that leads to the accumulation of metabolic waste products, including urea. Hemodialysis is a renal replacement therapy that functions to remove metabolic waste and maintain fluid balance in the body. Measurement of blood urea levels before and after hemodialysis is important to evaluate the effectiveness of the therapy. This study aimed to determine the comparison of blood urea levels before and after hemodialysis in patients with chronic kidney disease at Majenang Regional General Hospital. This study was a quantitative study with an observational analytic design using secondary data obtained from medical records of chronic kidney disease patients undergoing hemodialysis at Majenang Regional General Hospital during June–November 2025. A total of 103 patients who met the inclusion and exclusion criteria were included in the study. Data were analyzed using the Kolmogorov-Smirnov normality test and Paired Sample t-Test with a 95% confidence level. The results showed that the mean blood urea level before hemodialysis was 133.54 ± 38.13 mg/dL, with a minimum value of 29 mg/dL and a maximum value of 244 mg/dL. After hemodialysis, the mean blood urea level decreased to 46.51 ± 21.61 mg/dL, with a minimum value of 6 mg/dL and a maximum value of 102 mg/dL. The Kolmogorov-Smirnov test indicated that the data were normally distributed (p>0.05). The Paired Sample t-Test revealed a statistically significant difference between blood urea levels before and after hemodialysis (p=0.000). In conclusion, hemodialysis is effective in reducing blood urea levels in patients with chronic kidney disease. Measurement of blood urea levels before and after hemodialysis can be utilized as a laboratory parameter to evaluate treatment effectiveness and assist in monitoring the clinical condition of patients with chronic kidney disease..